Nano Online 2016
DOI: 10.1515/nano.11671_2015.222
|View full text |Cite
|
Sign up to set email alerts
|

Application of functional quantum dot nanoparticles as fluorescence probes in cell labeling and tumor diagnostic imaging

Abstract: Quantum dots (QDs) are a class of nanomaterials with good optical properties. Compared with organic dyes, QDs have unique photophysical properties: size-tunable light emission, improved signal brightness, resistance against photobleaching, and simultaneous excitation of multiple fluorescence colors. Possessing versatile surface chemistry and superior optical features, QDs are useful in a variety of in vitro and in vivo applications. When linked with targeting biomolecules, QDs can be used to target cell biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…[1] They possess supremely advantageous optical properties including a very high and stable fluorescence intensity that is strongly resistant to photobleaching. [2] In addition, they are known for their broad excitation spectrum and narrow emission profile enabling efficient multiplexing. [3] Based on these features QDs have been promoted as eminent materials for in vivo and in vitro biomedical applications such as tumor visualization and intracellular trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…[1] They possess supremely advantageous optical properties including a very high and stable fluorescence intensity that is strongly resistant to photobleaching. [2] In addition, they are known for their broad excitation spectrum and narrow emission profile enabling efficient multiplexing. [3] Based on these features QDs have been promoted as eminent materials for in vivo and in vitro biomedical applications such as tumor visualization and intracellular trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] QDs have gained broad application in many areas of biology. 28 The versatile properties of QDs have allowed investigators to conduct biological studies with extended spatiotemporal capabilities. 29 Liu et al have revealed extensive tumor heterogeneity at the molecular, cellular, and architectural levels by the multiplexed QDs and wavelength-resolved spectral imaging for molecular mapping of tumor heterogeneity on human prostate cancer tissue specimens.…”
mentioning
confidence: 99%
“…Over the past two decades, QDs have been subjected to extensive studies, mostly for their luminescence characteristics and surface properties. Several QD types are now being applied in diverse fields such as bioimaging or electronics, where they are, respectively, used as biomarkers (Bilan, Fleury, Nabiev, & Sukhanova, 2015;M.-X. Zhao & Zeng, 2015), or as constituents in LCD screens (J.…”
Section: General Discussion On Metal Oxide Npsmentioning
confidence: 99%